Two new species of Hypoxylon (Hypoxylaceae) from China based on morphological and DNA sequence data analyses - Song, Zikun; Pan, Xiaoyan; Li, Changtian; Ma, Hai-Xia; Li, Yu (Phytotaxa, 2022)
Two new species, Hypoxylon larissae and Hypoxylon jianfengense, are described and illustrated on the basis of a combination of morphological and molecular characters from China. Hypoxylon larissae was collected from southwest China (Yunnan province), while H. jianfengense was collected from southern China (Hainan province). Hypoxylon larissae is characterized by effused-pulvinate stromata, Orange (7) and Luteous (12) pigments extracted in 10% KOH and light brown to dark brown ascospores with straight germ slit. It is phylogenetically and morphologically closely related to H. fenderi. Hypoxylon jianfengense is distinguished by tubular to long tubular perithecia, Dark Green (21), Isabelline (65) and Dull Green (70) pigments extracted in 10% KOH and conspicuous coil-like perispore ornamentation. Hypoxylon jianfengense clustered with H. invadens and H. trugodes in a well-supported clade. Phylogenetic analyses of multi-gene sequences (ITS-LSU-RPB2-TUB2) support the recognition of the taxa as distinct.